2022
DOI: 10.1007/s11831-022-09825-5
|View full text |Cite
|
Sign up to set email alerts
|

Differential Evolution and Its Applications in Image Processing Problems: A Comprehensive Review

Abstract: Differential evolution (DE) is one of the highly acknowledged population-based optimization algorithms due to its simplicity, user-friendliness, resilience, and capacity to solve problems. DE has grown steadily since its beginnings due to its ability to solve various issues in academics and industry. Different mutation techniques and parameter choices influence DE's exploration and exploitation capabilities, motivating academics to continue working on DE. This survey aims to depict DE's recent developments con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 241 publications
0
9
0
Order By: Relevance
“…Another classic algorithm is CS; this is a bio-inspired algorithm on parasite nurseries of certain types of cuckoo birds; it is widely applied due to its ease of adaptation to different problems; it has also been modified on a large number of occasions [51]- [53]. One of the most potent and versatile evolutionary optimizers is the differential evolution algorithm, which, despite being more than two decades old, is used in various applications [54], [55] and continues to attract researchers to design modifications that improve its performance [56], [57]. The Grey Wolf Optimizer has been extensively used for a wide range of optimization problems due to its remarkable advantages over other swarm intelligence algorithms: it is easy to use, scalable, and has the unique ability to balance the exploration and exploitation in a way that promotes a favorable convergence during the search process [58].…”
Section: Metaheuristicsmentioning
confidence: 99%
“…Another classic algorithm is CS; this is a bio-inspired algorithm on parasite nurseries of certain types of cuckoo birds; it is widely applied due to its ease of adaptation to different problems; it has also been modified on a large number of occasions [51]- [53]. One of the most potent and versatile evolutionary optimizers is the differential evolution algorithm, which, despite being more than two decades old, is used in various applications [54], [55] and continues to attract researchers to design modifications that improve its performance [56], [57]. The Grey Wolf Optimizer has been extensively used for a wide range of optimization problems due to its remarkable advantages over other swarm intelligence algorithms: it is easy to use, scalable, and has the unique ability to balance the exploration and exploitation in a way that promotes a favorable convergence during the search process [58].…”
Section: Metaheuristicsmentioning
confidence: 99%
“…Once all trial vectors are produced, a greedy selection between each couple of target vectors and its corresponding trial vector is applied [13]. Since its introduction in 1995 by Storn and Kenneth [35], the DE algorithm has become an essential method for a large number of real problems or benchmarks, such as engineering domains [34], image processing [36], system parameters identification [37], robust control of nonlinear systems [38], and power scheduling problems [39][40][41]. In the aforementioned references, the performance and effectiveness of DE-based methods have been investigated and evaluated, and it has been shown that DE can perform better than other well-known population-based techniques such as GA and PSO.…”
Section: Multi Objectivementioning
confidence: 99%
“…Its straight forward execution, simple and small structure, and quick convergence can be considered the main reasons for its great efficiency. It has been successfully applied to a wide range of real-life applications, such as image processing [18,19], industriel noise recognition [20], bit coin price forecasting [21], optimal power flow [22], neural network optimization [23], engineering design problems [24], and so on. There are also several other fields like controlling theory [25,26] which are also open for the application of the DE algorithm.…”
Section: Introductionmentioning
confidence: 99%